Human Dignity, State Punishment, and Reciprocal Justice: A Comparative Mubādalah Perspective from Indonesia and South Korea - Zuliza Mohd Kusrin Rashi; Muhammad Rujaini Tanjung (Journal of Islamic Mubadalah, 2026)
This article examines how human dignity, state punishment, and reciprocal justice shape death penalty policies in Indonesia and South Korea, despite both countries being States Parties to the International Covenant on Civil and Political Rights (ICCPR). This study aims to explain why comparable constitutional commitments and international legal obligations have produced divergent death penalty policies by employing a comparative socio-legal approach informed by the Mubādalah perspective. The study adopts a qualitative research design integrating Retentionism–Abolitionism Theory, International Human Rights Norm Diffusion Theory, Legal Implementation Theory, and the Mubādalah perspective. Data were obtained from national legislation, constitutional court decisions, international human rights instruments, reports published by human rights organizations, and scholarly literature. The findings show that Indonesia continues to maintain a retentionist framework despite the suspension of executions since 2016, whereas South Korea has developed a de facto abolitionist practice reflecting the internalization of the right-to-life norm. This study affirms that the legitimacy of the death penalty should be assessed on the basis of legal validity, reciprocal recognition of human dignity, proportional state authority, and balanced justice. The Mubādalah perspective enriches the study of comparative criminal law and international human rights law.